RANCANG BANGUN SISTEM LAMPU MEJA MULTI-MODE DENGAN MENGGUNAKAN ESP32 - Muhammad Iqbal Alfarizi; Yuliarman Saragih; Reni Rahmadewi (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
Advances in science and technology play a role in realizing a better human life. one of them is theadvancement of electronic technology that has been inherent in human life. Studying diligently is anobligation of a learner, not only to pursue an achievement, but learning also helps to be more focusedon doing something. However, not a few people easily experience fatigue in studying, one of which isfatigue in the eyes, this fatigue arises due to the lack of lighting in the room where we study. Lightingrequirements are regulated based on the decree of the minister of health No. 48 of 2016 regarding theamount of irradiation needed to be able to carry out activities effectively and SNI 6197: 2020 wherevarious kinds of activities and work carried out have the required lighting standards. In this study,looking for the set point value and the amount of lux needed to be accessible through the androidapplication, looking for the amount of pwm value needed for each % of the manual setting of thelamp, and looking for the size of the voltage input measured in each test.